Effect of graphite addition on impregnated diamond bit properties - Lanlan Xie; Liyi Chen; Xiaolin Huang (Сверхтвердые материалы, 2019)
Graphite was used as a solid lubricant to reduce thermal damage in diamond bit when drilling without coolant. Graphite was added to the bit matrix material to reduce friction coefficient and heat. The influence of content, granularity, and surface metallization of graphite on the mechanical property and dry friction properties of the matrix, as well as the effect of diamond lifetime in the working layer were studied. Results showed that the hardness, bending strength, and friction coefficient of matrix gradually decreased with the increase in graphite concentration. Для зменшення термічного пошкодження алмазного інструмента при бурінні без охолоджуючої рідини в якості твердого мастила використовували графіт, його додавали до матеріалу матриці інструмента для зменшення коефіцієнта тертя і виділення тепла. Досліджено вплив вмісту, зернистості і металізації поверхні графіту на механічні властивості та умови сухого тертя матриці, а також часу утримання алмазу в робочому шарі. Результати показали, що твердість, міцність на вигин і коефіцієнт тертя матриці поступово зменшуються зі збільшенням концентрації графіту. Для уменьшения термического повреждения алмазного инструмента при бурении без охлаждающей жидкости в качестве твердой смазки использовали графит, его добавляли к материалу матрицы инструмента для уменьшения коэффициента трения и выделение тепла. Исследовано влияние содержания, зернистости и металлизации поверхности графита на механические свойства и условия сухого трения матрицы, а также времени удержания алмаза в рабочем слое. Результаты показали, что твердость, прочность на изгиб и коэффициент трения матрицы постепенно уменьшаются с увеличением концентрации графита.